The 54-kD protein of signal recognition particle contains a methionine- rich RNA binding domain (The Rockefeller University Press, 1990)
Signal recognition particle (SRP) plays the key role in targeting secretory proteins to the membrane of the endoplasmic reticulum (Walter, P., and V. R. Lingappa. 1986. Annu. Rev. Cell Biol. 2:499- 516). It consists of SRP7S RNA and six proteins. The 54-kD protein of SRP (SRP54) recognizes the signal sequence of nascent polypeptides. The 19-kD protein of SRP (SRP19) binds to SRP7S RNA directly and is required for the binding of SRP54 to the particle. We used deletion mutants of SRP19 and SRP54 and an in vitro assembly assay in the presence of SRP7S RNA to define the regions in both proteins which are required to form a ribonucleoprotein particle. Deletion of the 21 COOH- terminal amino acids of SRP19 does not interfere with its binding to SRP7S RNA. Further deletions abolish SRP19 binding to SRP7S RNA. The COOH-terminal 207 amino acids of SRP54 (M domain) were found to be necessary and sufficient for binding to the SRP19/7S RNA complex in vitro. Limited protease digestion of purified SRP confirmed our results for SRP54 from the in vitro binding assay. The SRP54M domain could also bind to Escherichia coli 4.5S RNA that is homologous to part of SRP7S RNA. We suggest that the methionine-rich COOH terminus of SRP54 is a RNA binding domain and that SRP19 serves to establish a binding site for SRP54 on the SRP7S RNA.